UNESCO as a Red Cross or as a notary of World Heritage? Structures, scale-related interactions and efficacy of UNESCO’s World Heritage regime - Schmitt, Thomas (2015)
The adoption of the World Heritage Convention by the UNESCO General Conference in 1972 marked the creation of an international regime for the protection of cultural and natural objects, sites and landscapes of outstanding universal value. Despite the vast number of academic publications relating to heritage – especially in Geography and related disciplines – there has to date been no independent analysis in the Anglophone literature on the World Heritage system using regime theory categories borrowed from International Relations. The paper attempts to close this gap by examining the World Heritage regime, its mechanisms and effects. In particular it systematizes the various effects of global regime authorities at World Heritage sites and landscapes, and interactions between global and local actors. This approach could also be significant for the discussion of glocalization phenomena.
Keywords: International regimes; World Heritage; UNESCO; glocalisation; Political Geography; Geographies of Heritage